Dos cedros aos pampas : imigração sírio-libanesa no Rio Grande do Sul, identidade e assimilação (1890-1949) - Francisco, Júlio César Bittencourt (2017)
This thesis refers to the history and the memory of Syrian-Lebanese immigration in Rio Grande do Sul, in the period from the last decade of the nineteenth century to the 1940s, more precisely between the years of 1890 and 1949, a temporal lapse that corresponds to two generations of immigrants, between their arrival in the country, adaptation to the new land and integration with the ‘gaucho’ culture. It aims to contribute to the knowledge of the origins of the Arab immigration in the state, the periods in which immigrants arrived, their places of fixation, the activities they carried out, the sociability’s they built, the institutions they founded, especially in Porto Alegre. The analysis is based on the use of diverse sources, such as books and periodicals; primary source documentation gathered in historical archives and museums; interviews; academic, memoirist and biographical literature; as well as websites and electronic documentation found on the internet. From a methodological point of view, the use of oral history as a privileged instrument for the production, analysis and interpretation of data and information made possible collected and highlight testimonies given by Arab descendants residing in Rio Grande do Sul. To situate the Levantine immigrant of the late nineteenth and early twentieth centuries, in a Middle East plunged in transnational issues, the work initially addresses the period of disintegration of the Ottoman Empire, the implementation of the French Mandate in Syria and Lebanon as well as the consequences of such fate in Porto Alegre. The independence of Lebanon and Syria in the 1940's closes the research chronological period. It was tried to demonstrate how these immigrants, coming from the Middle East, inserted and adapted in Rio Grande do Sul amid an environment dominated by other more numerous migratory waves, how they manage building their spaces of sociability’s and its path. The main result of the research was the certainty that the greatest asset of the Syrian and Lebanese descendants is the belonging to the gaucho culture, which they are inserted, without, however, loose their Lebanese or Arab identity, with all the meanings and representations that this implies.